Hubungan Kausalitas antara Sentimen Investor dan Pasar Keuangan Indonesia - Elizabeth Inge Pratiwi; Elsa Imelda (Jurnal Ekonomi, 2022)
This study aims to see the causal relationship that occurs between investor sentiment-based google search and the Indonesian stock-bond market in 2020. The test used in this study is a combined test between the quantile test to see the effect of investor sentiment on optimistic (pessimistic) conditions and the Granger causality test to detect the causal relationship that occurs between variables. The results of the study found that there was a one-way relationship between investor sentiment and the Indonesian stock market where investor sentiment affects the stock market. Interestingly, in the bond market, causal relationship between variables can’t be found. This study also found that the causal relationship between investor sentiment variables and financial markets only occurs when the optimistic and pessimistic conditions of investors aren't in extreme conditions.